2019
DOI: 10.1186/s13568-019-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth improvement of Lolium multiflorum Lam. induced by seed inoculation with fungus suspension of Xerocomus badius and Serendipita indica

Abstract: In this study, a pot experiment was carried out in greenhouse to investigate the potentials of Xerocomus badius and Serendipita indica to penetrate and colonize roots of ryegrass (Lolium multiflorum Lam.) and to induce beneficial effects on seed germination and seedling growth. The results showed that X. badius and S. indica successfully colonized in the root system of L. multiflorum seedlings and the root colonization rate was 72.65% and 88.42%, respectively. By microscopy, the hyphae, chlamydospores and spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
4
10
0
Order By: Relevance
“…The current results are in accordance with the findings of other researchers, wherein seeds treated with a conidial suspension of PGPF resulted in enhanced disease protection against the invading pathogens in many crop plants [9,11,12,54]. The induction of resistance offered by PGPF is ascribed to the ability of PGP traits that, in turn, alter the metabolic pathways that help the host plants to defend against the invading pathogens [14,50].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current results are in accordance with the findings of other researchers, wherein seeds treated with a conidial suspension of PGPF resulted in enhanced disease protection against the invading pathogens in many crop plants [9,11,12,54]. The induction of resistance offered by PGPF is ascribed to the ability of PGP traits that, in turn, alter the metabolic pathways that help the host plants to defend against the invading pathogens [14,50].…”
Section: Discussionsupporting
confidence: 92%
“…The obtained results were in corroboration with other studies, wherein antagonistic studies were regarded as the primary criteria to select the positive isolates for their evaluation against disease resistance during host-pathogen interaction in many crop plants [10,49,50]. Further, the antagonistic nature exhibited by PGPF is attributed to hyper parasitism, antibiosis (synthesis of antibiotics), production of lytic enzymes or competition for space and nutrients, which directly help in the management of invading pathogens [12,15,[49][50][51]. The qualitative analysis on the production of PGP traits confirmed that all the selected antagonistic isolates were positive for IAA, except NBP-44 and NBP-65, which were found negative for all the other traits evaluated.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the findings from the tolerance test of X. badius and the verified mutualistic symbiosis between L. multiflorum Lam. and X. badius driven by seed inoculation (Liu et al 2019 ), the effect of seed priming with spore suspensions of X. badius on seed germination and seedling growth of L. multiflorum Lam. were investigated under different salt and drought conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings from the tolerance test with X. badius and the verified mutualistic symbiosis between Lolium multiflorum Lam. and X. badius driven by seed inoculation (Liu et al 2019), we propose that X. badius is expected to enhance stress tolerance of L. multiflorum Lam. under drought and salt stresses.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation